SCHOOL AND FAMILY: REFLECTIONS ON A NECESSARY AND TIMELESS RELATIONSHIP - Morgado, Elsa Maria Gabriel; Rodrigues, João Bartolomeu; Silva, Levi Leonido Fernandes da (Cadernos de Educação Tecnologia e Sociedade, 2020)
The school and the family abundantly cross the central objectives and plans of their action and intervention in the educational community. This relationship more than necessary is now reportedly timeless, not only regarding the involvement of both within but also when it comes to the adoption of measures and strategies arising from the reality observed in a process always complex that is the act of educating someone. This article aims to show that the family assumes a previous preparation, continuous and complementary to school, while the school is assumed as the place where, par excellence, reinforce and complement knowledge, attitudes, values, and skills. The union of efforts and inter-institutional relationship strengthens and does not affect the identity of each of these deeply related partners. Therefore, with the framework, it is intended to finally reflect on the way to go for full involvement and desirable between the pairs.